Analisis Pengaruh Pembiayaan LPEI Konvesional dan Syariah, Variabel Ekonomi Makro Terhadap Pertumbuhan Ekspor Indonesia: - - Mohamad Mu’afa Taqiuddin Amir; Mohammad Bintang Pamuncak (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to evaluate the relationship between funding provided by LPEI in conventional and sharia forms to export growth, using two separate models to compare the two types of funding. This study also examines the relationship between inflation and the rupiah exchange rate on Indonesia's export growth. The analysis uses monthly data from 2015 to 2022 and ARDL approach in data analysis, with the help of EViews 12 to estimate the long-run and short-run impact of these variables on export growth. The results of this study show that in the short run, neither conventional nor sharia LPEI financing has a significant impact on export growth. The value of exports in the previous period and the previous two periods has a negative effect on current export growth. In contrast, export growth is positively affected by the value of exports in the previous three and four periods. Changes in the rupiah exchange rate in the previous period have a positive effect on export growth in the Islamic LPEI financing model, while changes in the inflation rate have no significant effect on export growth. In the long run, both conventional and Islamic LPEI financing do not have a major impact on export growth. The positive impact on export growth in the Islamic LPEI financing model is caused by fluctuations in the rupiah exchange rate in the long run. Changes in inflation do not have a significant impact on export growth based on other macroeconomic variables.